The problem of developing the green economy as a tool of sustainable development in Kazakhstan - Zhandar, A.N.; Asanbaeva, A.А.; Zhakypbek, A.M. (НАО «Карагандинский национальный исследовательский университет имени академика Е.А. Букетова», 2025)
The article examines the development of the green economy in Kazakhstan as a key factor in achieving the country’s sustainable development goals. An analysis of the current state of the green economy is presented, identifying the main challenges faced during its formation. The authors emphasize the need to strengthen government support and regulatory frameworks in the green economy sector. They also highlight the importance of education and training in green technologies and innovations, as well as the promotion of environmentally friendly practices among the population and the business community. Currently, Kazakhstan is actively developing eco-friendly technologies and striving for sustainable economic growth. In this context, government support, human capital development, innovation, and effective regulation play a crucial role in enhancing the country’s competitiveness and creating favorable environmental conditions for life and development. The article concludes with recommendations for advancing the green economy, including the introduction of new policies, programs, and investments. The research underscores the significance of developing a green economy in Kazakhstan to ensure sustainable growth, environmental protection, and the social well-being of the population.
Қазақстандағы тұрақты даму құралы ретіндегі жасыл экономиканы дамыту мәселесі
Проблема развития зеленой экономики как инструмента устойчивого развития в Казахстане
Keywords: green economy; sustainable development; concept; social development; economic sector; environment; environmentally friendly technologies; innovation